Principles of taxation : - Jones, Sally M. (McGraw Hill, 2011)
This text is appropriate for a one-semester introductory tax course at either the undergraduate or graduate level in which the instructor emphasizes business planning and decision-making. The content of the text is highly compatible with the AICPA Model Tax Curriculum and is ideal for preparing students to take the revised computer-based CPA exam